Albúmina y linfocitos en relación con el estado nutricional en los adultos mayores que acuden al Hospital Kokichi Otani de Vilcabamba - Piedra Palomino, Carolina Estefanía (2015)
Malnutrition is one of the factors that contribute in a global level to the morbidity. While each year in the population pyramids it is observed and increasing in its peak and decreasing in its base, it leads us to focus on the elderly. Malnutrition is common in this age group due to different factors present like the decreasing in food intake, anorexia, problems with chewing or swallowing, physiological changes among others and may be associated with increased mortality, loss of mobility, and even it can be the cause of increases in hospital budgets. Therefore a descriptive cross-sectional study was conducted in order to determine the levels of albumin and lymphocytes in relation to nutritional status in older people who come to Kokichi Otani Hospital of Vilcabamba, in Vilcabamba parish of Loja city, for which the albumin and the lymphocytes were quantified; nutritional status was known; and the results of the above related parameters were related. The sample was composed of 50 adults over 65 years old who met with the inclusion criteria and who signed the informed consent. Enzymatic colorimetric method for albumin was used, the number of lymphocytes was obtained by electrical impedance, and the physicians of the hospital applied to patients the nutritional assessment scale. As a result of this, 26% of them have hypoalbuminemia, 20% lymphopenia; 34% risk of malnutrition present. That is to say that when these parameters are related, the patients with risk of malnutrition presented decreased albumin and lymphocyte levels. Keywords: albumin, lymphocytes, nutritional assessment scale, elderly and risk of malnutrition.